EVALUTION OF MICROBIAL ACTIVITY IN ORGANIC SOLID FRACTION DURING COMPOSTING PROCESS TO BIOFERTILIZER USING COMPOSTING BIN METHODS - Aseel N. A.; F. M. Hassan; N. H. Hyder (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The current study aim to evaluating the composting in bins for organic fraction municipal solid waste and tracking the changes in physio-chemical and microbial characteristics such as Temperature, pH, C/N ratio and total viable count, total streptomyces, total coliform and pathogenic microorganisms as total Salmonella Shigella count. Seven treatments were used in research into the quick composting of the organic fraction of municipal solid waste. Two Composting bins contained municipal solid waste (MSW) mixed with animal and poultry manure (3:1), (2:1), waste mixture (2:1:1), and agricultural waste mixed waste. On the first day of composting, the pH was slightly acidic, then increased to alkaline, as EC . Microbiological parameters such as Total viable count are reduced during the thermophilic phase. They increased at the cooling phase , for TSC proliferation occurred in alkaline pH during composting and reached 4.1 CFU/g at maturation in composting bin 7. In conclusion, all composting bins developed a thermophilic phase, all had narrow alkaline pH with EC in some treatments less than 4mS.Cm-1, and C/N reached the desired ratio as stable compost,also microbiological parameters fluctuate with temperature.